Analysis of Reliability and Validity of a Questionnaire about Personal Learning Environments (PLE) - Chaves-Barboza, Eduardo (2018)
The study began with a pilot application a questionnaire (CPLE1, 78 items Likert related to personal learning environments) to 56 students of the course Technology Applied to Education of the University of Granada (Spain). This application allowed analyzing the reliability of the instrument and the effect of the elimination of some items on its reliability, by Cronbach alpha coefficient. An analysis of the internal consistency of the instrument by Corrected Homogeneity Index was also carried out. The study continued with the application of a guide to assess the content validity of the questionnaire (GVCPLE1). The results obtained with the implementation of this guide with ten experts were analysed using the Osterlind Congruity Index and through coding and categorization processes, which allowed suggestions that were incorporated, and a second validated questionnaire (CPLE2) was designed. This study shows how the access to the field has been accomplished; it makes a characterization of the students involved in the pilot study and of the expert participants in the validity analysis. Also, the statistical assumptions and the methodologies that were applied in the analysis are explained.